Job satisfaction, work engagement and stress/burnout of elderly care staff: a qualitative research: Job satisfaction, work engagement and stress/burnout of elderly care staff - Foà, Chiara; Guarnieri, Maria Cristina; Bastoni, Giorgia; Benini, Barbara; Giunti, Olimpia Maria; Mazzotti, Manola; Rossi, Cristina; Savoia, Alessandra; Sarli , Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. Faced with the widespread use of services and facilities for the care and assistance of the elderly, the aim of this study was to explore the factors that can affect job satisfaction, work engagement and stress / burnout of the professionals who work there. Method. 32 semi-structured interviews were administered to a not probabilistic sample of the different professional roles (coordinators, nurses, healthcare assistants, physiotherapists, community animators) of a Human Services Company in Reggio Emilia (Italy). This includes day-care and residential care facilities for the elderly. Results. The thematic content analysis showed that inter-professional collaboration and positive relationships with superiors, colleagues and elderly people favour the job satisfaction, while workload, high responsibilities, reduction of rest periods and contributory inequity create dissatisfaction. The work engagement is favoured by professional autonomy, a sense of belonging, professional growth, specific training, while it is disadvantaged by scarce career opportunities, job insecurity and low recognition of one’s contribution. Finally, inadequate pay, work load, high turnover and strong emotional experiences related to elderly people increase work-related stress/burnout, while working autonomy, psychological support and good relationships with the elderly reduce it. Some specificities were found according to the different professional roles and the type of services offered. Discussion and conclusions. The results suggest organizational improvement strategies that take these factors into account. Among the improvement proposals we highlight, for example, the promotion of training events, a greater involvement of personnel in corporate decisions and an adequate psychological support for professionals.